2016
DOI: 10.1016/j.mce.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor profiling and activity in cardiac myocytes

Abstract: Estrogen signaling appears critical in the heart. However a mechanistic understanding of the role of estrogen in the cardiac myocyte is lacking. Moreover, there are multiple cell types in the heart and multiple estrogen receptor (ER) isoforms. Therefore, we studied expression, localization, transcriptional and signaling activity of ERs in isolated cardiac myocytes. We found only ERα RNA (but no ERβ RNA) in cardiac myocytes using two independent methods. The vast majority of full-length ERα protein (ERα66) loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 65 publications
(107 reference statements)
3
41
1
1
Order By: Relevance
“…Additionally, we previously described that ER transcript expression is quite low, restricted to ERα and not sexually dimorphic in cardiac myocytes, 32 prompting our interest in understanding what other pathways are involved in mediating the functional sex differences we observed at baseline. However, differences in hormone signaling between the sexes could be a source of variation leading to the genetic and functional differences in the myocytes.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, we previously described that ER transcript expression is quite low, restricted to ERα and not sexually dimorphic in cardiac myocytes, 32 prompting our interest in understanding what other pathways are involved in mediating the functional sex differences we observed at baseline. However, differences in hormone signaling between the sexes could be a source of variation leading to the genetic and functional differences in the myocytes.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study, which reported the presence of ERα and a lack of ERβ expression in cardiomyocytes [36] prompted us to initially focus on ERα. This was accomplished by generating a tamoxifen-inducible cardiomyocyte-specific ER α knock out mouse (cs-ERαKO), as detailed in the Material and Method section.…”
Section: Resultsmentioning
confidence: 99%
“…5,21,22 Our results showed that the expression level of ERa mRNA and ERb mRNA was similar between women and men and this is consistent with other studies describing no sex differences in the expression of ERs in human 22 and in animal heart. 23 An upregulation of ERa at both mRNA and protein level was associated with human aortic stenosis and with the end-stage human heart failure due to dilated cardiomyopathy. 21 In both cases, ERa was expressed at a comparable concentration in women and in men, and the increase in ERa occurred in both.…”
Section: Discussionmentioning
confidence: 99%